Correction: Graphene material preparation through thermal treatment of graphite oxide electrochemically synthesized in aqueous sulfuric acid. Issue 34 (24th May 2018) - Gurzęda, B.; Buchwald, T.; Nocuń, M.; Bąkowicz, A.; Krawczyk, P.
Abstract : Correction for 'Graphene material preparation through thermal treatment of graphite oxide electrochemically synthesized in aqueous sulfuric acid' by B. Gurzęda et al., RSC Adv., 2017, 7, 19904–19911.